HUBUNGAN KUALITAS SPERMA PADA PEROKOK BERAT DAN BUKAN PEROKOK PADA MAHASISWA - Sisca Devy (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2018)
Smoking is a major source of free radicals that can cause various health problems, one of which is a disorder of male fertility.This study aims to determine the influence of cigarette and sperm quality in heavy smokers and nonsmokers at FK students UISU 2015. The study design was observational analytic study is to find the relationship between the free variable with variable tied to using cross sectional study approach of independent variables and the dependent variable. As the case in this study were heavy smokers and nonsmokers with normal sperm quality comparison according to the WHO in 2010 and the category of heavy smokers according PDPI > 600 stems per year. These results indicate male heavy smokers experiencing abnormal sperm quality is higher than non-smokers with normal value based on the comparison of sperm volume 10 heavy smokers (62.5%) non-smokers 15 people (93.8%) and also heavy smokers sperm motility 4 the (25.0%) and non-smokers 15 (93.8%) and sperm morphology also heavy smokers 3 (18.8%) and non-smokers 16 (100.0%). It can be concluded that there is a relationship of smoking with sperm quality.